1997
DOI: 10.2527/1997.75123262x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous profiles and within-day variations of metabolites and hormones in cows fed diets varying in alimentary supplies before short-term feed deprivation.

Abstract: We investigated continuous profiles and within-day variations of some metabolites and hormones in four nonpregnant, nonlactating cows fed hay-based diets in two equal meals. Diets supplied either too much or too little N (approximately 1.3 or .8 times the maintenance requirements) and NE1 (approximately 1.2 or .8 times). Continuous collection of ruminal liquor, blood, and urine samples was performed for 42 consecutive hours, the last 16 h covering a period without feed. For twice-daily feeding, nitrogenous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…As summarized in Table 2, urinary 3MH excretion during days 10–14 of treatments was not different between treatments. However, Ndibualonji et al . (1997) showed that urinary 3MH excretion in non‐lactating cows was increased by 1.5‐fold during days 21–28 of treatments of energetic underfeeding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As summarized in Table 2, urinary 3MH excretion during days 10–14 of treatments was not different between treatments. However, Ndibualonji et al . (1997) showed that urinary 3MH excretion in non‐lactating cows was increased by 1.5‐fold during days 21–28 of treatments of energetic underfeeding.…”
Section: Resultsmentioning
confidence: 99%
“…Harris and Milne (1981) reported that intravenously administered radioactive 3MH was quantitatively excreted in cattle urine for 5–7 days. Ndibualonji et al . (1997) showed that urinary 3MH excretion and plasma 3MH concentration were increased during days 21–28 of an energetic underfeeding treatment, and indicated that endogenous protein mobilization was greater in energy‐restricted cows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study the moderate concentrations of SCFA in cows fed 60% concentrates (see Table 3) are probably related to the period of feed restriction discussed above. Ndibualonji et al (1997) examined the continuous profiles and within-day variations of SCFA in 4 non-lactating cows fed twice daily (6:15 a.m. and 3:30 p.m.). These authors observed that, with the beginning of a meal and over the next 6 hours (postprandial period), the ruminal SCFA increased.…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%